Effects of thiopental in cold ischemia in liver transplantation: An experimental study - Büyük, Başak; Karakoç, Ebru (Journal of Surgery and Medicine, 2019)
Aim: The aim of this study is to use the reducing effect of thiopental on metabolic rate to reduce basal metabolic rate and thus energy requirements in organs with doses administered before organ transplantation and in this way to increase organ viability by reducing to a minimum tissue damage occurring during the cold ischemia process. Methods: The study was started with 20 Wistar albino rats in 2 groups. In Group 1 (Control=Ketamine-Xylazine group) and Group 2 (Thiopental group), rats had a midline incision made after shaving the abdominal region under anesthesia with appropriate agents. The portal vein was entered with a cannula and organ storage solution at +4 °C was injected to the portal vein to perfuse the liver. Then hepatectomy was performed, the livers were placed in Falcon tubes containing +4°C organ storage solution and stored at +4°C. Tissue samples were taken for histopathologic and TUNEL investigation and storage solution samples were taken for biochemical analysis at 12th hour. Results: In histopathologic evaluation, the mean for hydropic degeneration and sinusoidal dilatation was higher in Group 1 compared to Group 2, but the results weren’t statistically significant. Apoptotic Index (AI) values in Group 1 were higher than Group 2; however, there was no statistically significant difference between the median values (3.50 (Min:1.00-Max:16.00) vs. 2.50 (Min:1.00-Max:20.00), respectively p=0.974). The mean values for ALT, AST and ALP were appeared to be higher in Group 1. Conclusion: In conclusion, thiopental has a protective effect on liver tissue during the cold ischemia process via reducing the mean values of histopathological, apoptotic and biochemical assessment results, but these findings weren’t statistically significant.